Rule based Stemmer for Marathi Language - Pise, N; Gupta, V (International Journal of Computer Sciences and Engineering, 2025)
Natural Language Processing (NLP) is a branch of artificial intelligence which deals with the analysis and synthesis of natural languages in the form of text and speech. NLP requires stemming algorithms to remove derivational and inflectional affixes without performing morphological analysis of the inputs. These algorithms are essential to extract root or stem words. The goal of stemming is to reduce word forms/grammatical forms to their root forms. To accomplish, specific knowledge of language is required. In NLP, the stemmer can be used to improve the efficiency of text summarization, text mining, information retrieval and sentiment analysis. In this paper, we proposed a rule based stemming approach for Marathi language using Marathi corpus, stopword list and suffix stripping rules.